Reflecting on dignity in the lawyer-client relation in a pro bono environment - Santos, S. (Law and Society Association Annual Meeting, 2019)
In democratic societies access to justice and to courts are a constitutional right, but also a way to guarantee equality among citizens, regardless of their social or economic status. Citizens in a situation of social or economic fragility like refugees, immigrants, unemployed, victims of domestic or sexual violence, prostitutes, among others, are those who are more likely to demand justice from the margins, with less capacity to understand juridical proceedings and more in need of the work of lawyers. The access to justice for these populations can be understood as a form to achieve dignity and to help them in the process of social inclusion. In these paper, we would like to reflect on dignity by proposing that it can be understood as a relational concept emphasizing the relation between lawyer and client in a situation of non-payment for the juridical services. The institutionalization of pro bono and the influence of corporate social responsibility discourses and metrics inside the law firm can challenge this notion of dignity. From an ethical form of professionalism based on the idea of helping others in an individual and non-organized way, to a commercial form of professionalism integrated and promoted by the firm where pro bono activities become another standard of internal and external evaluation. Methodologically, we conducted interviews with lawyers in solo practice and in law firms with pro bono policies and collected CSR reports from those firms.